Bridging Knowledge: The Practice of Academic Freedom in Indonesia - Rahayu, Rahayu; Roisah, Kholis; Wardana, Khansadhia Afifah (PDIH Untag Semarang, 2024)
This article aims to analyze the current practices of academic freedom in Indonesia, driven by the premise that academic freedom is a cornerstone for every scholar with their expertise to seek, explore, innovate, and develop knowledge without intervention from certain parties. This concept is deeply rooted in the freedoms of thought, opinion, and expression in public, which are integral to the framework of human rights. This article is a study employing a normative juridical approach, attempting to examine the relevant legislation and actual circumstances. The data used is secondary data, focusing on various types of literature that explore the complex relationship between academic freedom, human rights, and democracy. The research findings indicate that in Indonesia, regulations governing academic freedom are enshrined in Law No. 12 of 2012 on Higher Education, Law No. 14 of 2005 on Teachers and Lecturers, and Law No. 20 of 2003 on the National Education System. Nevertheless, instances of persecution and dismissal of academic staff often occur on grounds of threatening nationalism or possessing subversive ideologies that ultimately disturb public security. The coordinator of the Indonesian Caucus for Academic Freedom cites several cases attacking academic freedom, such as cyber-attacks, repression of student actions, and criminalization of academics who speak out against corruption and for academic freedom, such as those involving Saiful Mahdi from Syiah Kuala University and Ubedillah Badrun from the State University of Jakarta (UNJ). This article aims to uncover the issues arising in the practice of academic freedom and the alignment between existing regulations and the human rights framework, using a normative juridical method. Academic freedom must serve as the foundation for the development of knowledge for the nation's welfare.